Chronic cardiovascular toxicity in the older oncology patient population. Issue 5 (September 2019) - Findlay, Simon G.; Gill, Jason H.; Plummer, Ruth; DeSantis, Carol; Plummer, Chris
Abstract: Survivorship statistics demonstrate that the incidence of cancer continues to rise worldwide, with a further 60% increase in diagnoses predicted by 2030 attributed to lifestyle risk factors, screening programmes resulting in earlier diagnosis but also the changing demographics of the population. More than a third of new cancer diagnoses and almost half of cancer survivors are now aged 70 years or older. Despite this increasing incidence, worldwide five-year cancer survival rates have improved significantly over the past two decades. After cancer, cardiovascular disease is the second most common cause of death in developed countries. With continued improvements in overall prognosis, patients with cancer have an increased exposure to cardiovascular risk factors resulting in higher cardiovascular morbidity and mortality, particularly in older patients. This relationship between cancer and cardiovascular disease is not surprising as they share the common risk factors of aging, smoking, obesity, and poor diet. In this review, we discuss the toxicity of cancer treatments on the cardiovascular system, particularly in older patients. We focus primarily on radiotherapy and anthracycline chemotherapy because of their chronic adverse effects and appraise approaches toward the detection and treatment of this toxicity to maximise survival and quality of life of older patients with cancer.